1970
DOI: 10.15581/003.25.36162
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the image of immigration in prime time television fiction

Abstract: This article presents the results of a research study into the image of immigration as presented in television fiction, taking Cultivation Theory as a reference. Content analysis was performed on a representative sample of prime-time fictional programming broadcast in 2010 on six television channels. Results show that immigrant characters are under-represented and their construction is based on negative stereotypes. These results are discussed in relation to the role of television fiction in reducing prejudice. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

1970
1970
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…With respect to the third objective (to describe the representation of neo-archetypes from the perspective of family relationships), in the field of narrative persuasion, the study has found that identification with the protagonists sponsors and helps to change attitudes in society. That is, when viewers resemble a fictional character, they empathise with them and acquire their perspective from a cognitive and affective point of view, changing their identity occasionally or permanently and experiencing a situation of cognition, which leads to changes in beliefs and opinions, as Igartua, Barrios and Ortega (2012) or Moyer-Gusé, Chung and Jain (2011) have already expressed. In this way, the neo-archetypes of the family are in line with the new forms of family diversity with established ties that, de facto, are emerging in society: from three-parent families, to homoparental, single-parent or nuclear families, dinkies or even the concept of the urban tribe for raising children, are increasingly glimpsed and exposed in the selected cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…With respect to the third objective (to describe the representation of neo-archetypes from the perspective of family relationships), in the field of narrative persuasion, the study has found that identification with the protagonists sponsors and helps to change attitudes in society. That is, when viewers resemble a fictional character, they empathise with them and acquire their perspective from a cognitive and affective point of view, changing their identity occasionally or permanently and experiencing a situation of cognition, which leads to changes in beliefs and opinions, as Igartua, Barrios and Ortega (2012) or Moyer-Gusé, Chung and Jain (2011) have already expressed. In this way, the neo-archetypes of the family are in line with the new forms of family diversity with established ties that, de facto, are emerging in society: from three-parent families, to homoparental, single-parent or nuclear families, dinkies or even the concept of the urban tribe for raising children, are increasingly glimpsed and exposed in the selected cases.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research highlights that a bias is produced in the cases of social minorities (Igartua, Barrios and Ortega, 2012;Mastro, 2009) or new social trends (Markov & Yoon, 2021). Thus, more and more fiction series are being produced with the aim of attenuating certain characteristics and creating a series of innovative content and representations, with protagonists and characters who carry out actions that are normally pigeonholed as other behaviour types (Lozano, 2020).…”
Section: Television Series and The Generation Of Stereotypes And Arch...mentioning
confidence: 99%
“…Content analysis studies have shown that there is a low presence of ethnic minority or immigrant characters in fictional television contents (Igartua, Barrios & Ortega, 2012). Furthermore, they usually have relatively unimportant roles in the narrative structure of fictional programs and are represented in a distorted or stereotyped way (Greenberg, Mastro & Brand, 2002;Harwood & Anderson, 2002;Mastro, 2009aMastro, , 2009bMastro & Behm-Morawitz, 2005).…”
Section: Ethnic Minorities and Immigrants In Television Fictionmentioning
confidence: 99%
“…Studies carried out in Spain regarding immigration and television fiction have shown that immigrant characters are predominantly represented as low-skilled and illegal; there is a high presence of immigrants acting as criminals; and only infrequently do immigrants have a central role in the narrative plots (Galán, 2006;Lacalle, 2008;Ruiz-Collantes et al, 2006). Moreover, foreign-immigrant characters are also portrayed showing more violent behavior and being on the receiving end of more acts of violence than natives and they are also defined as less hard-working, intelligent or tolerant (Igartua, Barrios & Ortega, 2012).…”
Section: Ethnic Minorities and Immigrants In Television Fictionmentioning
confidence: 99%
See 1 more Smart Citation